Main Factors in the Development of Tourism.Touristic Resources of Uzbekistan - Toirov Amirkhon (Zien Journals, 2022)
This article talks about the main factors in the development of tourism, the fact that tourism is a highly profitable industry for the country, and the specific features of management in the field of tourism.
Keywords: management; prospective networks; international tourism; sanatorium-resort organizations